Molecular insights into psychedelic drug action. Issue 1 (1st December 2021) - Slocum, Samuel T.; DiBerto, Jeffrey F.; Roth, Bryan L.
Abstract: A confluence of factors has renewed interest in the scientific understanding and translational potential of psychedelic drugs such as lysergic acid diethylamide (LSD), mescaline, and psilocybin: the desire for additional approaches to mental health care, incremental progress in basic and clinical research, and the reconsideration and relaxation of existing drug policies. With the United States Food and Drug Administration's designation of psilocybin as a "Breakthrough Therapy" for treatment‐resistant depression, a new path has been forged for the conveyance of psychedelics to the clinic. Essential to the further development of such applications, however, is a clearer understanding of how these drugs exert their effects at the molecular level. Here we review the current knowledge regarding the molecular details of psychedelic drug actions and suggest that these discoveries can facilitate new insights into their hallucinogenic and therapeutic mechanisms. Abstract : In this article we review the current understanding of the molecular details of psychedelic drug effects. We provide information from the atomic to the cellular level and integrate this information into a model of psychedelic drug actions.